Progressive mitochondrial dysfunction in cerebellar synaptosomes of cystatin B-deficient mice - Gorski, Katarin; Jackson, Christopher B.; Nyman, Tuula A.; Rezov, Veronika; Battersby, Brendan J.; Lehesjoki, Anna-Elina (Frontiers in Molecular Neuroscience, 2023)
The involvement of mitochondrial dysfunction in cystatin B (CSTB) deficiency has been suggested, but its role in the onset of neurodegeneration, myoclonus, and ataxia in the CSTB-deficient mouse model (Cstb-/-) is yet unknown. CSTB is an inhibitor of lysosomal and nuclear cysteine cathepsins. In humans, partial loss-of-function mutations cause the progressive myoclonus epilepsy neurodegenerative disorder, EPM1. Here, we examined cerebellar synaptosomes from early symptomatic Cstb-/- mice to identify the molecular mechanisms involved in the onset of CSTB-deficiency associated neural pathogenesis. Proteome analysis showed that CSTB deficiency is associated with differential expression of mitochondrial and synaptic proteins. Using respirometry, we revealed that there was a progressive impairment in mitochondrial function coinciding with the onset of myoclonus and neurodegeneration in Cstb-/- mice. This mitochondrial dysfunction was not associated with alterations in mitochondrial DNA copy number or membrane ultrastructure. Collectively, our results show that CSTB deficiency generates a defect in synaptic mitochondrial bioenergetics that coincides with the onset and progression of the clinical phenotypes, and thus is likely a contributor to the pathogenesis of EPM1.